2011
DOI: 10.1038/eye.2011.143
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of blindness and other smoking-related diseases and its impact on motivation for smoking cessation in eye patients

Abstract: Purpose Cigarette smoking is a major cause of morbidity and mortality. The association between smoking and eye diseases is less widely recognised relative to other betterknown smoking-related conditions. This study aims to assess the awareness and fear of known smoking-related diseases among current smokers attending an ophthalmology outpatient clinic and to evaluate their relative impact on the likelihood of smoking cessation. Patients and methods A cross-sectional survey using a structured interview of rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…Handa et al looked at patients attending an Eye Clinic where less than half of the patients were aware that smoking is linked with blindness. 1 This was previously shown to a similar extent in other studies. [2][3][4][5] Our study looked at eye disease in general rather than blindness, and differed from previous studies as it targeted a different patient group: a Smoking Cessation Clinic rather than an Eye Clinic.…”
Section: Discussionsupporting
confidence: 76%
“…Handa et al looked at patients attending an Eye Clinic where less than half of the patients were aware that smoking is linked with blindness. 1 This was previously shown to a similar extent in other studies. [2][3][4][5] Our study looked at eye disease in general rather than blindness, and differed from previous studies as it targeted a different patient group: a Smoking Cessation Clinic rather than an Eye Clinic.…”
Section: Discussionsupporting
confidence: 76%
“…The main source of non-occupational cadmium exposure is tobacco smoking and food (Satarug et al, 2010; Satarug and Moore, 2004). Although the evidence is sufficient, the public awareness of smoking-related ocular risks is relatively low compared with other diseases (Bidwell et al, 2005; Handa et al, 2011; Ng et al, 2010); education of such knowledge could help tobacco control (Asfar et al, 2015). Previous studies reported that the “smoking causes blindness” label on cigarette packages used in Australian anti-smoking campaign did increase the smoker’s awareness of risk of blindness, and prompt them to quit smoking (Kennedy et al, 2012; Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study reported that blindness evoked the same fear as, or more fear than, lung cancer, heart disease, and stroke, and a large number of smokers would be highly motivated to quit smoking if they knew they would develop early signs of blindness. 83 …”
Section: Patient Education and Increasing Amd Awarenessmentioning
confidence: 99%